Pengenalan Akupunktur Sebagai Terapi Pendukung Untuk Diabetes dan Hipertensi - Maria Magdalena Riyaniarti Estri wuryandari; Hartati Tuna; Nita Damayanti; Suwarno Suwarno (Jurnal Medika: Medika, 2025)
Diabetes mellitus and hypertension are two chronic diseases whose prevalence continues to rise in Indonesia and significantly impact the quality of life of those affected. Conventional medical therapy often requires supportive approaches to enhance treatment effectiveness and improve patients' quality of life. Acupuncture, as a form of traditional Chinese medicine, has shown potential in regulating glucose metabolism and reducing blood pressure through neuroendocrine mechanisms and improved blood circulation. This community service activity aims to provide education and acupuncture services as a supportive therapy for people with diabetes and hypertension in the Larangan Utara village area, Tangerang. The activity method includes health counseling, consultation sessions, and periodic acupuncture therapy. The results of the activity indicate a positive response from the participants, both in terms of understanding the diseases and the reduction of subjective complaints related to blood pressure and blood sugar levels. It is hoped that this program can serve as a model for integrating complementary therapies in the promotional and preventive efforts of public health services.